2011
DOI: 10.1186/1472-6963-11-262
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experience of choosing an outpatient clinic in one county in Denmark: results of a patient survey

Abstract: BackgroundResearch on patients' choice of hospital has focused on inpatients' rather than outpatients' choice of provider. We have investigated Danish outpatients' awareness and utilisation of freedom of choice of provider; which factors influence outpatients' choice of hospital, and how socio-demographic variables influence these factors in a single uptake area, where patients were free to choose any public hospital, where care was provided free at the point of delivery, and where distance to the closest hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
(27 reference statements)
2
18
0
2
Order By: Relevance
“…Perhaps the most important finding from the point of view of future health-care policy is the relative importance or influence that factors other than providers' outcomes have on patients' choice. This is consistent with recent quantitative studies from Denmark and the Netherlands, which also found the factors influencing patients were shorter waiting times [29][30][31] ; shorter distance to the hospital 29,30.32 ; the views of GPs 30 and patients' previous experience of the facility. [29][30][31] Two studies in England have reported the influence of distance 33 and the reputation of the provider.…”
Section: Comparison With Previous Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…Perhaps the most important finding from the point of view of future health-care policy is the relative importance or influence that factors other than providers' outcomes have on patients' choice. This is consistent with recent quantitative studies from Denmark and the Netherlands, which also found the factors influencing patients were shorter waiting times [29][30][31] ; shorter distance to the hospital 29,30.32 ; the views of GPs 30 and patients' previous experience of the facility. [29][30][31] Two studies in England have reported the influence of distance 33 and the reputation of the provider.…”
Section: Comparison With Previous Researchsupporting
confidence: 91%
“…This is consistent with recent quantitative studies from Denmark and the Netherlands, which also found the factors influencing patients were shorter waiting times [29][30][31] ; shorter distance to the hospital 29,30.32 ; the views of GPs 30 and patients' previous experience of the facility. [29][30][31] Two studies in England have reported the influence of distance 33 and the reputation of the provider. 18 This growing body of literature lends weight to the rather limited impact that provider performance data might be expected to have on patient choice.…”
Section: Comparison With Previous Researchsupporting
confidence: 91%
“…Patients attending Groote Schuur Hospital (GSH), the only tertiary hospital included among the INR clinics, travelled a median distance of 18.2 km (1.6 km–50.8 km), which was noticeably further than the median road distance of 3.60 km travelled by patients overall to treatment facilities. Reasons for this may include a possible perception of higher quality care or convenience associated with GSH, if located near to a place of employment [ 22 ]. The overall proportion of patients within the target INR therapeutic range was 50.3 %.…”
Section: Discussionmentioning
confidence: 99%
“…In specialist and hospital care, there are as of yet no studies conducted in Sweden on how patient choice rights are used (which are weaker in this sector since they are not legally sanctioned) by different groups. Studies from other Nordic countries as well as the UK indicate, however, that the better-educated use this right more actively than those with lower education (Ringard, 2012;Birk et al, 2011;Dixon et al, 2010).…”
Section: Choice In Health Carementioning
confidence: 93%